Peningkatan Aktivitas Belajar Mahasiswa Pada Mata Kuliah Geomorfologi Melalui Metode Kolaboratif - Kontekstual Dalam Kegiatan Lesson Study - Nurin Rochayati; Mas`ad Mas`ad; Agung Pramunarti; Ahmad Affandi; Arif Arif (Journal Prakarsa Paedagogia, 2018)
Collaborative-contextual learning strongly emphasizes group activities, learning interactions, and collaboration between students in carrying out tasks. In learning with collaborative-contextual methods directed so that students can be actively involved, by conducting learning activities such as presenting assignments, paying attention to explanations from lecturers or colleagues, discussing, asking questions, expressing opinions, and answering questions. The aim of collaborative-contextual learning to be achieved is to improve learning activities and student participation in geomorphology learning. The method used in this study is a qualitative method with a descriptive approach and action. The target in this study as the research subjects were 21 students in the third semester who took geomorphology courses. Data collection method using observation (observation sheet), test (question / case study), and documentation (photo, video). Data analysis using interactive analysis. Based on the data obtained from the research results it can be concluded that, the stages of collaborative-contextual learning that have been applied have successfully involved students actively during the learning process. This is because, all stages of learning activities emphasize the involvement of students from the beginning to the end of learning. Students become more active, the learning atmosphere becomes more conducive, group discussion becomes more lively because all group members prepare the discussion material well. They also became more enthusiastic and active in every lesson. With better quality learning, students' understanding of the learning process becomes good and understanding of the lecture material also becomes better